The Art of Community: A Key for Sustaining Coffee Shop Business in Pontianak - Angga Permadi Karpriana; Syahbandi Syahbandi; Juanda Astarani; Muhammad Fahmi; Djunita Permata Indah; Ahmadi Ahmadi; Eko Supriyanto (Journal of International Conference Proceedings, 2024)
This research is aimed to explaining the phenomenon of the large number of coffee shop businesses in the city of Pontianak due to the Coffee Culture owned by residents in Pontianak specially and in general in Kalimantan Barat. This type of research is qualitative research with an ethnography approach with a research time span from 2021-2024. Data was obtained in several stages such as distributing questionnaires, in-depth interviews with three coffee shop actors in Pontianak and collecting related documents as a literature review to reveal the phenomenon that happened. The research results show that perception, motivation, appearance of coffee, experience, beliefs, attitudes and coffee brands play an important role in the formation of today's coffee culture. On the other hand, coffee business actors to be able to compete and maintain their business, they increase hospitality to increase customer loyalty to be able to maintain their business even by targeting quite specific markets in certain groups that focus with product, price, place, promotion, people and presentation.